Black and white, skin and masks, the body in Caribbean art. Readings from Frantz Fanon - Wood, Yolanda (2022)
Black and white are more than colors, they are keys to a symbolic contrast on islands that built their social structure –since colonial times– on slavery that racialized social relations and generated with them various forms of discrimination that continue to this day. One of the important contributions of black to the visual arts of the Caribbean is its color, a visual sign in the universe of racial tensions, born in the very heart of modern–colonial society. This work aims to distinguish that trajectory of visual meanings, through a selection of works that use black and white from the physical support of the body with all its expressive capacities. One of the most significant texts of the twentieth century on the issue, Black Skin, White Masks (1952) by Frantz Fanon, will be assumed as a resource of critical interpretation for the study of the selection of works and authors from the insular Caribbean that are inscribed in the conflicts of the racialization and inferiorization of corporeality, to explore forms of a decolonizing humanism, "to return man to his place", to reposition his "I" and to revalue his place in history.